Autoconciencia inteligencia emocional - Goleman, Daniel (BookaVivo, 2022)
Self-awareness is the most important component of emotional intelligence and involves having a deep understanding of our emotions, strengths, weaknesses, needs, and drives. But you won't be able to achieve full self-awareness by just using regular feedback and self-reflection. This book will teach you to understand your thoughts and emotions, to persuade your colleagues to share what they really think of you, and to establish more productive and rewarding relationships with your employees and bosses.
Online resource; title from title details screen (O'Reilly, viewed May 18, 2022)
Keywords: Self-actualization (Psychology); Decision making; Success; Prise de décision; Succès; decision making; Downloadable audio books; Audiobooks; Livres audio